IDENTIFIKASI, PREVALENSI DAN INTENSITAS PARASIT IKAN GABUS (Channa striata) YANG DIPELIHARA PADA KOLAM BUDIDAYA DI DESA GARUNG KABUPATEN PULANG PISAU KALIMANTAN TENGAH - Maryani, Maryani; Monalisa, Shinta Sylvia; Effriadi, Chandra (Universitas Teuku Umar, 2023)
The study aims to identify the kind of infestation that infects local fisheries biota in the region of the city's waters and knows the prevalence and intensity of the ektoparasite found. Examined as many as eight species of birch (oxyeleotris marmorata), as many as 30 (botias macracanthus), one cork (channa striata), as many as 1 tail, and the patin fish (Scylla SPP), as many as 7. Traces of ectoparasites found include dactylogyrus sp, tricodina sp, lernea sp, epistylis sp, oodinium sp and octolasmis spp.